Upaya Meningkatkan Kemampuan Bahasa Inggris pada Anak di Panti Asuhan Yayasan Rumah Bakti Kasih Anak Indonesia - Suhairani Lusri Lubis; Fajar Utama Ritonga (Yayasan Literasi Sains Indonesia, 2023)
The family is the source of education that children receive for the first time. The family is the nuclear family consisting of mother, father and children. As soon as a child is born, the first person he is close to and what he knows is family. But not all children are lucky, can live and live in their families. One place that accommodates these less fortunate children is an orphanage. In the orphanage there will be many children who live together who are cared for by the caretaker of the orphanage. Because the number of children is not proportional to the number of administrators in the orphanage, it causes a lack of attention received by children, especially in terms of helping the teaching and learning process. The children at the orphanage are still lacking in learning, but they have the enthusiasm to learn. It's just that there are several factors that become inhibiting factors in gaining knowledge. Therefore it really needs help and the role of various parties to help the process of forming children's character, one of which is in terms of education. The target to be achieved is to improve the English skills of the children in the orphanage by selecting 6 children in the orphanage and this activity uses the casework method by Zastrow and at the assessment stage uses the Focus Group Discussion technique. The results obtained from this activity were progress in terms of English which was felt by each child and their report card scores were better than before.